PENGARUH AUDIT SWITCHING DAN AUDIT TENURE TERHADAP AUDIT DELAY PADA PERBANKAN SYARIAH DI INDONESIA - Elena Zulinovika; Usdeldi Usdeldi; Ferri Saputra Tanjung (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Every business in Indonesia needs to make financial reports at the end of each quarter to be used as a guide in managing expenses. In accordance with Financial Accounting Standards 1 of 2015. For users of financial reports, the speed of completing reports is quite important. The speed at which a business entity publishes its financial reports to the general public and the OJK is a factor that influences how quickly the auditor can complete the audit. The aim of this research is to find out whether auditor switching and audit tenure have anything to do with audit delays in sharia banks operating at OJK from 2018 to 2022. The research target population is all sharia banks operating at OJK from 2018 to 2022. By using purposive sampling technique, thirty (30) data were selected as samples. This research uses quantitative methods using secondary data obtained from the official website of Islamic banks. Data analysis tool with eviews 12. In contrast, the most commonly used data mining technique is panel data regression analysis. Research findings show that audit switching and audit tenure have an effect on audit delay. Meanwhile, audit switching and audit tenure simultaneously influence audit delay. The corrected r-squared coefficient of determination is 0.222967, indicating that all independent variables contribute 22.29% to the explanation of the dependent variable.